Imidazole and Azo-Based Schiff Bases Ligands as Highly Active Antifungal and Antioxidant Components - Siham Slassi; Adeline Fix-Tailler; Gérald Larcher; Amina Amine; Abdelkrim El-Ghayoury (Heteroatom Chemistry)
We describe, herein, the synthesis, full characterization, and optical properties of four different ligands L1-L4 which associate an azo group, an imidazole unit, and a Schiff base fragment. The UV-visible absorption bands are characteristic of π→π⁎ and n→π⁎ transitions with an additional charge transfer between the azobenzene moiety and the imino group. Finally the determination of MIC80 values against pathogenic fungi such as S. apiospermum, A. fumigatus, and C. albicans revealed that these ligands have effective antifungal properties with highest activities (MIC80) on C. albicans for the azole based ligands L1-L3. DPPH radical scavenging of the studied ligands was also tested.